2017
DOI: 10.1038/srep44935
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Gastric Microbiota After H. Pylori Eradication and in Different Histological Stages of Gastric Carcinogenesis

Abstract: The role of bacteria other than Helicobacter pylori (HP) in the stomach remains elusive. We characterized the gastric microbiota in individuals with different histological stages of gastric carcinogenesis and after receiving HP eradication therapy. Endoscopic gastric biopsies were obtained from subjects with HP gastritis, gastric intestinal metaplasia (IM), gastric cancer (GC) and HP negative controls. Gastric microbiota was characterized by Illumina MiSeq platform targeting the 16 S rDNA. Apart from dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
137
4
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(176 citation statements)
references
References 27 publications
25
137
4
7
Order By: Relevance
“…Additionally, with the deletion of Helicobacter , the relative abundance of Lactobacillus , Prevotella , Streptococcus , Acinetobacter , Bacteroides, and Bifidobacterium was increased at 24 weeks after eradication therapy. Consistently, a previous study from Hong Kong showed that the one‐week course of H pylori eradication also resulted in an increase in bacterial diversity and restoration of the relative abundance of other bacteria to levels similar to those of individuals without H pylori . The predicted functional analysis revealed that the inflammation‐associated pathways, including lipopolysaccharide biosynthesis and lipopolysaccharide biosynthesis proteins, were inactivated in the post‐eradication group compared to the baseline group, which supports the idea that H pylori eradication improves gastric mucosal active inflammation and reduces chronic inflammation to some extent …”
Section: Discussionsupporting
confidence: 85%
“…Additionally, with the deletion of Helicobacter , the relative abundance of Lactobacillus , Prevotella , Streptococcus , Acinetobacter , Bacteroides, and Bifidobacterium was increased at 24 weeks after eradication therapy. Consistently, a previous study from Hong Kong showed that the one‐week course of H pylori eradication also resulted in an increase in bacterial diversity and restoration of the relative abundance of other bacteria to levels similar to those of individuals without H pylori . The predicted functional analysis revealed that the inflammation‐associated pathways, including lipopolysaccharide biosynthesis and lipopolysaccharide biosynthesis proteins, were inactivated in the post‐eradication group compared to the baseline group, which supports the idea that H pylori eradication improves gastric mucosal active inflammation and reduces chronic inflammation to some extent …”
Section: Discussionsupporting
confidence: 85%
“…In general, Helicobacter rRNA reads constituted 91.0% to 99.0% of all bacterial rRNA reads in the H. pylori-positive samples, except in sample Atr8 (56.7%), while in the individuals scored as H. pylori negative, the proportion of Helicobacter reads ranged from 4.7% to as many as 63.2% of all bacterial rRNA reads. Similar observations have been reported previously (5,7,8,16), but in contrast to the case for previous studies, our findings represent actual expressed sequences and imply that these bacteria are viable and transcriptionally active, although they still could constitute a transient population. However, since these samples were derived from tissue biopsy specimens, to be detected by the method used in this paper, such transient bacteria would still need to be attached to the surface, speaking in favor of an established population rather than a transient one.…”
Section: Resultscontrasting
confidence: 57%
“…When Helicobacter was included in the analysis, genus richness was not significantly different (P ϭ 0.4983), while the diversity and evenness estimates of the communities drastically changed (P Ͻ 10 Ϫ10 ; specifically, for Shannon diversity P ϭ 1.75e Ϫ15 , for Simpson diversity P ϭ 5.586e Ϫ14 , and for evenness P ϭ 1.436e Ϫ11 ), resulting from lower diversity indices for the H. pylori-positive individuals than for the H. pylori-negative individuals due to the very high abundance of Helicobacter rRNA. Notably, earlier studies of the stomach microbiota based on sequencing of DNA as opposed to RNA have indicated substantially higher taxonomic diversity (5,8,9). However, many of these taxa exist in very limited quantities and are likely to be transcriptionally inactive, suggesting that their influence on the gastric ecosystem may be insignificant.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this seems to be a reversible situation. Although the diversity of the gastric microbiota is highest in healthy uncolonised individuals, post H pylori eradication, the diversity can increase to the level observed in controls …”
Section: Resultsmentioning
confidence: 97%